SPEECH SAMPLES AS ONE OF THE EFFECTIVE WAYS OF ENRICHING SCHOOLCHILDREN'S SPEECH - Alimsaidova Sayyora , (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article reveals the main aspects of using speech patterns used in speech to build new, thoughtful and interesting phrases for the interlocutor.